Why man creates. - Kaiser Aluminum and Chemical Corporation (Santa Monica, Calif. : Pyramid Films, 1968)
Demonstrates in its form and content, the nature of the creative process and discusses the variety, richness, and importance of creative vision.
Keywords: Creation (Literary, artistic, etc.); Creative ability